COMPARISON OF ANTI BACTERIAL EFFICACY OF PHOTODYNAMIC THERAPY AND DOXYCYCLINE ON AGGREGATIBACTER ACTINOMYCETEMCOMITANS - Setiawatie, Ernie Maduratna; Lestari, Vina Puji; Astuti, Suryani Dyah (African Journal of Infectious Diseases (AJID), 2018)
Background: Aggregatibacter actinomycetemcomitans (A.actinomycetemcomitans) is an anaerobic bacterium has been frequently associated with aggressive periodontitis. Photodynamic therapy (PDT) is a medical treatment to prevent infection progression that utilizes light to activate a photosensitizing agent. Doxycycline is an antibacterial having pho-tosensitivity. This study aimed to evaluate potential doxycycline as an antibacterial and photosensitizer combine PDT against A.actinomycetemcomitans bacteria. Material and methods: Samples were distributed to 4 groups as follow: (1) Groups A treated with a diode laser, (2) Group B treated with doxycycline 0,1% and laser, (3) Group C treated only with Doxycycline 0.1%, and (4) Group D no exposure doxycycline/laser. Data were analyzed by one-way ANOVA and Tukey’s HSD test at 5% significance level. Results: In this study, doxycycline 0.1% has the effect of reducing the bacterial viability of (59.60±3.26%). Whereas laser exposure 120 s combined with doxycycline produce the effect of bacterial viability reduction (88.50±2.83%) is not significantly different from the effect of laser 120 s exposure (88.79±2.60%). In clinical treatment, the application of laser exposure is generally at the duration of the exposure time of 30 s. The results of this study indicate that the du-ration of laser exposure 30 s shows a reduction in bacterial viability (44.91±1.69%) equal to the laser and with a com-bination of doxycycline and laser exposure (70.70±2.43%). So at low doses of laser exposure, doxycycline 0.1% com-bined with the laser results in the greatest reduction in bacterial viability, significantly different from laser exposure alone. Conclusion: at low doses of laser exposure (30s with energy 3.68 J/cm2), doxycycline 0.1% combined with the laser results in the greatest reduction in bacterial viability, significantly different with laser exposure alone.